A Single Chance to Contact Multiple Targets: Distinct Osteocyte Morphotypes Shed Light on the Cellular Mechanism Ensuring the Robust Formation of Osteocytic Networks. Issue 5 (6th July 2016) - Fritz, Alan; Bertin, Ariana; Hanna, Patricia; Nualart, Francisco; Marcellini, Sylvain
ABSTRACT: The formation of the complex osteocytic network relies on the emission of long cellular processes involved in communication, mechanical strain sensing, and bone turnover control. Newly deposited osteocytic processes rapidly become trapped within the calcifying matrix, and, therefore, they must adopt their definitive conformation and contact their targets in a single morphogenetic event. However, the cellular mechanisms ensuring the robustness of this unique mode of morphogenesis remain unknown. To address this issue, we examined the developing calvaria of the amphibian Xenopus tropicalis by confocal, two‐photon, and super‐resolution imaging, and described flattened osteocytes lying within a woven bone structured in lamellae of randomly oriented collagen fibers. While most cells emit peripheral and perpendicular processes, we report two osteocytes morphotypes, located at different depth within the bone matrix and exhibiting distinct number and orientation of perpendicular cell processes. We show that this pattern is conserved with the chick Gallus gallus and suggest that the cellular microenvironment, and more particularly cell–cell contact, plays a fundamental role in the induction and stabilization of osteocytic processes. We propose that this intrinsic property might have been evolutionarily selected for its ability to robustly generate self‐organizing osteocytic networks harbored by the wide variety of bone shapes and architectures found in extant and extinct vertebrates.